A Study on n-Derivation in Prime Near – Rings - Adhab, Enaam Farhan (Iraqi Journal of Science, 2020)
The main purpose of this paper is to show that zero symmetric prime near-rings, satisfying certain identities on n-derivations, are commutative rings.